Root and tuber crops: Untapped potential for food and nutrition security and rural livelihood development in Myanmar. Results of a scoping study. - Aung, M. (International Potato Center, 2018)
The objectives of the Myanmar scoping study are: To collect, collate and analyse existing secondary information on RTC area, production, processing, marketing, and consumption at the national and state/district levels where (a) RTC (root and tuber crops) production/consumption is most important and/or (b) where existing or pipeline IFAD investment projects are located. This will aim to locate RTCs in the context of wider livelihood systems. To collect, collate and analyse relevant information on diets, food consumption habits, and nutritional status of rural and urban men, women and children in target areas. To collect, collate and analyse additional information related to the development of climate change scenarios for RTCs. To identify key actors and stakeholders across public, private and civil society sectors, with whom FoodSTART+ can engage in both action research and policy inputs to improve the contribution of RTCs to food security. To identify key problems and opportunities for attention by FoodSTART+ in the context of partnership with relevant IFAD investment projects or development-oriented projects funded by other donors, and information gaps where further assessments on specific topics are justified.